Safe Implementation of Treatments in Stroke: a study on intravenous thrombolysis in patients over 80 years of age with acute ischaemic stroke - Manju Krishnan; Danilo Toni; Niaz Ahmed; Anand Dixit; Ana Paiva Nunes; Marius Matusevicius; Jose Egido; Letizia Concari; Monica Reggiani; Alain Pagès; Thierry Danays (BMJ Open)
Objectives To investigate the safety and efficacy outcomes of intravenous thrombolysis (IVT) in patients aged >80 years with acute ischaemic stroke (AIS) after IVT was approved in this patient population in several European and non-European countries during 2018–2019.Design This is an observational registry study using prospectively collected data from the Safe Implementation of Treatment in Stroke (SITS) registry. Comparisons will be performed between patients treated post-approval (July 2018 to December 2021) period with those treated pre-approval (June 2015 to June 2018) period using propensity score matching (PSM).Setting This is a multicentre international study in hospitals treating AIS with IVT.Participants Patients aged >80 years who otherwise followed the IVT Summary of Product Characteristics of European countries as part of the mutual recognition procedure.Primary and secondary outcomes The main outcomes were symptomatic intracerebral haemorrhage per SITS monitoring study definition, death and functional independency as defined by a modified Rankin Scale score of 0–2 at 90 days.Results After PSM, 614 patients remained in each group (mean age 87 years, 39% males). All baseline data were well balanced after PSM. There were no statistically significant differences in outcomes between pre- and post-approval patients for SICH (2.5% vs 2.3%, risk ratio (RR) 1.064, 95% CI 0.345–1.784), death (25.3% vs 28.4%, RR 0.889, 0.699–1.08) and functional independency at 90 days (40.3% vs 37%, RR 1.089, 0.942–1.237).Conclusions In this observational study of IVT treatment in patients >80 years of age with AIS before and after formal approval for this treatment, we did not find any difference in outcomes between the pre- and post-approval periods.